One‐Pot Polymerization Syntheses: Incorporating Bioactives into Poly(anhydride‐esters). Issue 16 (23rd June 2016) - Faig, Jonathan J.; Smith, Kervin; Moretti, Alysha; Yu, Weiling; Uhrich, Kathryn E.
Abstract : To reduce raw material consumption and increase synthetic efficiency, bioactive‐based poly(anhydride‐esters) containing aliphatic dicarboxylic acid‐linkages and bioactives, salicylic and p ‐hydroxybenzyl acid, are synthesized via one‐pot melt‐condensation polymerizations. One‐pot poly(anhydride‐esters) physicochemical characteristics, molecular weight, and thermal properties are analyzed and compared. One‐pot salicylic acid‐based poly(anhydride‐esters) are further evaluated against analogous polymers synthesized via established methods, possessing statistically similar polymer and thermal properties while drastically reducing reaction time and solvent usage. Interestingly, p‐ hydroxybenzyl acid‐based poly(anhydride‐ester) synthesis is temperature‐dependent, as higher reaction temperatures facilitate polyester formation. Compared to their poly(anhydride‐ester) analogs, these are found to possess improved thermal properties and higher molecular weight while. Accelerated hydrolytic degradation studies confirm complete bioactive release and polymer degradation. Furthermore, polymer cytotoxicity studies using 3T3 mouse fibroblasts show all polymers to be cytocompatible above therapeutically relevant concentrations. This method demonstrates that the synthesis of high‐yielding monomers can be followed by melt‐condensation polymerization in situ for the synthesis of polyanhydrides and their derivatives. Abstract : Bioactive‐based poly(anhydride‐esters) containing salicylic or p ‐hydroxybenzyl acid and aliphatic dicarboxylic acid‐linkages are successfully synthesized via one‐pot melt condensation polymerizations.